PENGARUH PEMAHAMAN, KESADARAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN DI KOTA BATAM - Youthy Simbolon; Hermaya Ompusunggu, S.E., M.Ak. (SCIENTIA JOURNAL, 2024)
Land and building tax in Batam City is used for the benefit of the general public in providing facilities or services so that taxpayer compliance in paying taxes is needed but compliance with land and building tax payments in Batam city is still fluctuating. Several factors that can affect taxpayer compliance include taxpayer understanding, taxpayer awareness and tax sanctions. The purpose of this study was to analyze the effect of taxpayer understanding, taxpayer awareness and tax sanctions on taxpayer compliance both partially and simultaneously. The method used in the analysis is a quantitative approach using multiple linear regression using the help of the SPSS 27 application, the type of data in this study is primary data obtained through distributing questionnaires through the google form platform. The results of the study partially show that taxpayer understanding has a significant positive effect on land and building taxpayer compliance in Batam City, tax awareness has no significant positive effect on land and building tax compliance in Batam City, tax sanctions have a significant positive effect on land and building tax compliance in Batam City. simultaneously Tax Understanding, Taxpayer Awareness and Tax Sanctions affect Land and Building Taxpayer Compliance in Batam City.